VD_FINDINFO Jug / 2012 / 90 vom 20. Oktober 2011 - VD Tribunal cantonal (2011)
COAUTEURDROIT PÉNAL, TRAVAIL D'INTÉRÊT GÉNÉRAL, TENTATIVEDROIT PÉNAL, VOLDROIT PÉNAL | 106 CP, 107 CP, 22 ad 139 CP, 19a LStup